PREDICTION THE SHELF LIFE OF INSTAN PORRIDGE FORTIFIED WITH CATHFISH (Pangasius hypopthalmus) PROTEIN CONCENTRATE USING DIFFERENT PACKAGING - Sinaga, Sopia Zefanya; ', Dewita; ', Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The aimed of this research was to predict the shelf life of instant porridge fortified with cathfish (Pangasius hypopthalmus) protein concentrate using aluminium foil and HDPE packaging coated with paperboard. The method used was Arrhenius with 25ºC dan 35ºC of temperatures storage. The parameters analyses were fat and peroxide value analyze. The result of this research showed that based on peroxide analyses the shelf life of instan poridge fortified with cathfish (Pangasius hypopthalmus) protein concentrate coated aluminium foil packaging in 25ºC temperature storage was 53,1154 days and for 35ºC temperature storage was 24,5895 days. HDPE packaging for 25ºC temperature storage was 61,0149 days and for 35ºC temperature storage was 41,9248 days.Keywords: Aluminium foil, Arrhenius, Catfish, HDPE, Instant porridge, Shelf life.